City Comedy, Public Style. (September 2016) - Hunter, Matthew
Abstract : London's expansion altered the structure of social relations within the city by making anonymity, rather than familiarity, a normative precondition of day‐to‐day encounters. This new condition had the vexing effect of making Londoners public to one another in a way that they had not been before: always present to and scrutinized by other strangers as strangers themselves. This essay proposes that the city comedies of Thomas Dekker, Ben Jonson, and John Marston offered a solution to this novel condition of anonymity by extolling various styles of theatrical dialogue as novel models of social competency within an urban environment newly and uncomfortably defined by publicity and anonymity. That social competency comes from the power of various styles to resolve, exploit, or even intensify the newly public shape of urban, social relations. In modeling the capacity of styles to negotiate public, urban life, London's city comedians were contending with the thoroughly public dimension of style itself. [M.H.]